3D spheroid-microvasculature-on-a-chip for tumor-endothelium mechanobiology interplay - Zhang, Yingqi (2024)
During the final stage of cancer metastasis, tumor cells embed themselves in distant capillary beds, from where they extravasate and establish secondary tumors. Recent findings underscore the pivotal roles of blood/lymphatic flow and shear stress in this intricate tumor extravasation process. Despite the increasing evidence, there is a dearth of systematic and biomechanical methodologies that accurately mimic intricate 3D microtissue interactions within a controlled hydrodynamic microenvironment. Addressing this gap, we introduce an easy-to-operate 3D spheroid-microvasculature-on-a-chip (SMAC) model. Operating under both static and regulated flow conditions, the SMAC model facilitates the replication of the biomechanical interplay between heterogeneous tumor spheroids and endothelium in a quantitative manner. Serving as anin vitromodel for metastasis mechanobiology, our model unveils the phenomena of 3D spheroid-induced endothelial compression and cell-cell junction degradation during tumor migration and expansion. Furthermore, we investigated the influence of shear stress on endothelial orientation, polarization, and tumor spheroid expansion. Collectively, our SMAC model provides a compact, cost-efficient, and adaptable platform for probing the mechanobiology of metastasis.